The Antimicrobial Activity of Quercus Infectoria Extracts Against Bacteria Isolated from Wounds Infection - Noor Ameer Hanon; Fouad Najm Abd (Al-Mustansiriyah Journal of Science)
Bacteria that cause wound infections were isolated and diagnosed from patients, who were hospitalized at the Martyr Al-Sadr Hospital from October 2019 to April 2020.  Antibacterial effect of Quercus infectoria extract (aqueous and alcoholic) on the isolated bacteria has been studied. The results showed that the alcoholic extract has a higher antibacterial effect than the aqueous extract against Gram-positive bacteria like Staphylococcus aureus, Staphylococcus epidermidis, and Staphylococcus saprophyticus except Micrococcus roseus, which the effect of aqueous extract was higher than alcoholic extract, whereas aqueous and alcoholic extracts showed the same effect against Streptococcus sp.. The alcoholic extract has higher antibacterial effect than the aqueous extract against Gram-negative bacteria (Escherichia coli, Pseudomonas sp., Enterococcus faecalis, Shigella dysnteriae, Enterobacter sakazkii, citrobcter freundii and Alcaligenes faecalis) except proteus sp., which the aqueous extract was higher than alcoholic extract.